1988
DOI: 10.1016/0883-9026(88)90018-3
|View full text |Cite
|
Sign up to set email alerts
|

Bank loan officers' perceptions of the characteristics of men, women, and successful entrepreneurs

Abstract: Much anecdotal evidence suggests that women, compared to similarly situated men, have great difficulty securing financing for entrepreneurial endeavors. In addition, a mounting body of evidence illustrates how women in managerial roles are perceived in terms of sex stereotypes rather than in terms of their accomplishments. The present study extends this line of research to investigate whether female entrepreneurs are also viewed in terms of sex stereotypes. One hundred and six bank loan officers evaluated eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
111
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 287 publications
(122 citation statements)
references
References 14 publications
2
111
0
9
Order By: Relevance
“…For example, Buttner and Rosen (1988) studied whether women lacking entrepreneurial characteristics caused discrimination. They found no evidence that bank officers' funding decisions were affected by stereotypes of the entrepreneur's gender.…”
Section: Literature Background Gender Differences In Financial Decisimentioning
confidence: 99%
“…For example, Buttner and Rosen (1988) studied whether women lacking entrepreneurial characteristics caused discrimination. They found no evidence that bank officers' funding decisions were affected by stereotypes of the entrepreneur's gender.…”
Section: Literature Background Gender Differences In Financial Decisimentioning
confidence: 99%
“…There is evidence that the decisions of the banks about loan requests are different for men and women, even when businesses are similar in terms of liquidity and solvency. Buttner and Rosen [16] found that banks perceive that men have more probability of business success than women. Other papers show that gender discrimination not only appears in the fi nal decision of granting of credit but also throughout the application and negotiation process, placing women at a disadvantage or discouraging them during that process [12], [75].…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Based on the importance of entrepreneurship, which contributes to the economy, and development of a country, research focusing on why a business fails to take off or does not sustain based on factors such as access to finance has been well established. Apart from that, the differences between men and women in starting and building a business are another area of focus in entrepreneurship (Buttner and Rosen, 1998). However, research focusing on women owned businesses and factors that affect them are still minimal (Hanafi, 2012).…”
mentioning
confidence: 99%